Exploring job hopping in Indonesian generation z: Grit, perceived organizational support, and job satisfaction - Aulia, Nurul; Daud, Ilzar; Marumpe, Dody Pratama (Junal Ilmu Manajemen, 2025)
The phenomenon of job hopping is a challenge for organizations today, especially within the Generation Z workforce in Indonesia. This study aims to examine the effects of grit and perceived organizational support on job-hopping intentions, with job satisfaction as a mediating variable. A quantitative method was used to collect data through questionnaires distributed to 200 Generation Z employees working in Indonesian companies for less than two years. Data analysis was conducted using structural equation modeling (SEM) with AMOS 26 software. The results indicate that grit has a significant positive relationship with job hopping intentions, while perceived organizational support shows a significant negative relationship with job hopping intentions. Additionally, job satisfaction mediates the relationship between grit, perceived organizational support, and job hopping intentions. These findings provide insights for organizations on how to increase job satisfaction and organizational support to reduce the intention of Generation Z employees in Indonesia to change jobs.